If tan 2 1 2 ° , tan 2 2 4 ° , tan 2 4 8 ° , and tan 2 9 6 ° are the roots of the polynomial f ( x ) = x 4 + A x 3 + B x 2 + C x + D , find A + 2 B + 3 C + 4 D .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wow, great solution!
That is an absolutely genius solution!
Using the identity tan 3 x = tan ( 6 0 ° − x ) tan x tan ( 6 0 ° + x ) , if x = 6 ° , then tan 1 8 ° = tan 5 4 ° tan 6 ° tan 6 6 ° , and since tan 1 8 ° = tan 7 2 ° 1 and tan 5 4 ° = tan 3 6 ° 1 , this can be rearranged to tan 3 6 ° = tan 6 ° tan 6 6 ° tan 7 2 ° .
Using the identity tan 5 x = tan ( 7 2 ° − x ) tan ( 3 6 ° − x ) tan x tan ( 3 6 ° + x ) tan ( 7 2 ° + x ) , if x = 6 ° , then tan 3 0 ° = tan 6 6 ° tan 3 0 ° tan 6 ° tan 4 2 ° tan 7 8 ° , and since tan 4 2 ° = tan 4 8 ° 1 and tan 7 8 ° = tan 1 2 ° 1 , this can be rearranged to tan 6 ° tan 6 6 ° = tan 1 2 ° tan 4 8 ° .
Combining these two equations gives tan 3 6 ° = tan 1 2 ° tan 4 8 ° tan 7 2 ° , so that tan 3 θ = tan θ tan 4 θ tan 6 θ is true for θ = 1 2 ° .
Since tan 3 6 ° = tan 6 ° tan 6 6 ° tan 7 2 ° is equivalent to − tan 3 6 ° = − tan 6 ° tan 6 6 ° tan 7 2 ° , and since − tan 6 ° = tan 9 6 ° 1 and − tan 3 6 ° = tan 1 4 4 ° , this can be rearranged to tan 7 2 ° = tan 2 4 ° tan 9 6 ° tan 1 4 4 ° , so that tan 3 θ = tan θ tan 4 θ tan 6 θ is true for θ = 2 4 ° .
Since tan 3 6 ° = tan 1 2 ° tan 4 8 ° tan 7 2 ° is equivalent to − tan 3 6 ° = tan 1 2 ° tan 4 8 ° ( − tan 7 2 ° ) , and since − tan 3 6 ° = tan 1 4 4 ° , tan 1 2 ° = tan 1 9 2 ° , and − tan 7 2 ° = tan 2 8 8 ° , this can be rearranged to tan 1 4 4 ° = tan 4 8 ° tan 1 9 2 ° tan 2 8 8 ° , so that tan 3 θ = tan θ tan 4 θ tan 6 θ is true for θ = 4 8 ° .
Since tan 3 6 ° = tan 6 ° tan 6 6 ° tan 7 2 ° is equivalent to tan 3 6 ° = ( − tan 6 ° ) tan 6 6 ° ( − tan 7 2 ° ) , and since tan 3 6 ° = tan 5 7 6 ° , − tan 6 ° = tan 9 6 ° 1 , tan 6 6 ° = tan 3 8 4 ° 1 , and − tan 7 2 ° = tan 2 8 8 ° , this can be rearranged to tan 2 8 8 ° = tan 9 6 ° tan 3 8 4 ° tan 5 7 6 ° , so that tan 3 θ = tan θ tan 4 θ tan 6 θ is true for θ = 9 6 ° .
Using the tangent identity equations with t = tan θ :
tan 2 θ = 1 − tan 2 θ 2 tan θ = 1 − t 2 2 t
tan 3 θ = tan ( 2 θ + θ ) = 1 − tan 2 θ tan θ tan 2 θ + tan θ = 1 − ( 1 − t 2 2 t ) t 1 − t 2 2 t + t = 3 t 2 − 1 t ( t 2 − 3 )
tan 4 θ = tan 2 ( 2 θ ) = 1 − tan 2 2 θ 2 tan 2 θ = 1 − ( 1 − t 2 2 t ) 2 2 ( 1 − t 2 2 t ) = t 4 − 6 t 2 + 1 4 t ( 1 − t 2 )
tan 6 θ = tan 2 ( 3 θ ) = 1 − tan 2 3 θ 2 tan 3 θ = 1 − ( 3 t 2 − 1 t ( t 2 − 3 ) ) 2 2 ( 3 t 2 − 1 t ( t 2 − 3 ) ) = ( 1 − t ) ( 1 + t ) ( t 2 − 4 t + 1 ) ( t 2 + 4 t + 1 ) 2 t ( t 2 − 3 ) ( 3 t 2 − 1 )
Substituting these into tan 3 θ = tan θ tan 4 θ tan 6 θ gives 3 t 2 − 1 t ( t 2 − 3 ) = t ⋅ t 4 − 6 t 2 + 1 4 t ( 1 − t 2 ) ⋅ ( 1 − t ) ( 1 + t ) ( t 2 − 4 t + 1 ) ( t 2 + 4 t + 1 ) 2 t ( t 2 − 3 ) ( 3 t 2 − 1 ) , which rearranges and simplifies to t 8 − 9 2 t 6 + 1 3 4 t 4 − 2 8 t 2 + 1 = 0 . Substituting x = t 2 gives x 4 − 9 2 x 3 + 1 3 4 x 2 − 2 8 x + 1 = 0 , which has the desired solutions of x = tan 2 1 2 ° , x = tan 2 2 4 ° , x = tan 2 4 8 ° , and x = tan 2 9 6 ° .
Therefore, A = − 9 2 , B = 1 3 4 , C = − 2 8 , D = 1 , and A + 2 B + 3 C + 4 D = 9 6 .
You have written the triple angle formula tan 3 x = tan ( 6 0 ° − x ) tan x tan ( 6 0 ° + x ) and the quintuple angle formula: tan 5 x = tan ( 7 2 ° − x ) tan ( 3 6 ° − x ) tan x tan ( 3 6 ° + x ) tan ( 7 2 ° + x )
I only knew about the former identitym, not the latter identity. Can we generalize this to the ( 2 n + 1 ) -tuple angle formula as well? Like is there a septuple angle formula, nonuple angle formula by expressing tan [ ( 2 n + 1 ) x ] in terms of product of tan ( x + k i ) for constants k i .
Log in to reply
I found the tan 5 x equation here . There's a short proof for it there that I must admit I don't quite follow, but maybe it can be generalized to other ( 2 n + 1 ) -tuple angles, which appears to be:
tan ( 2 n + 1 ) x = ( − 1 ) n k = 1 ∏ 2 n + 1 tan ( x + 2 n + 1 ( k − n − 1 ) 1 8 0 ° )
for positive integers n .
Log in to reply
It doesn't work for 2 n + 1 = 7
Log in to reply
@Pi Han Goh – Oops! I adjusted the equation with ( − 1 ) n . Try that.
Log in to reply
@David Vreken – Nope, not true either.
Log in to reply
@Pi Han Goh – It's working for me
Haha, I just spent 4 hours trying to prove this identity but I got nothing.
Maybe @Mark Hennings can save the day again. I won't mind posting a note about it .
Log in to reply
@Pi Han Goh – Yes, a note would be good
Log in to reply
@David Vreken – Done .
I was expecting your solution to be using some cyclic quadrilateral proof because 1 2 ∘ + 2 4 ∘ + 4 8 ∘ + 9 6 ∘ = 1 8 0 ∘ .
But it's still quite an eye-opener. I don't know the motivation behind setting up tan ( 3 θ ) = tan ( θ ) tan ( 4 θ ) tan ( 6 θ ) in the first place. It appears to come out of nowhere.
Log in to reply
It was mostly a result of some math "doodling" I was doing. Using the tan 3 x and tan 5 x equations, I came up with tan 3 6 ° = tan 1 2 ° tan 4 8 ° tan 7 2 ° (as shown in my solution). I thought it was unusual that all the angles were multiples of 1 2 , so I wondered what other angles fulfilled the equation tan 3 θ = tan θ tan 4 θ tan 6 θ and came up with the above problem.
I did notice that 1 2 ° + 2 4 ° + 4 8 ° + 9 6 ° = 1 8 0 ° , but I'm not sure if that was just a coincidence. Another fun fact is that the roots of f ( x ) = x 4 − 9 2 x 3 + 1 3 4 x 2 − 2 8 x + 1 include all solutions of tan 2 2 n ⋅ 1 2 ° for integers n ≥ 0 , since the angles just repeat themselves modulus 1 8 0 ° .
Problem Loading...
Note Loading...
Set Loading...
Let's first convert all the angles to radians, 1 2 ∘ → 1 5 π , 2 4 ∘ → 1 5 2 π , 4 8 ∘ → 1 5 4 π , 9 6 ∘ → 1 5 8 π
The equation cos ( 5 X ) = − 2 1 has roots 1 5 2 π , 1 5 4 π , 1 5 8 π , 1 5 1 0 π , 1 5 1 4 π .
Using quintuple angle formula, cos ( 5 X ) = 1 6 cos 5 ( X ) − 2 0 cos 3 ( X ) + 5 cos ( X ) . Let y = cos ( X ) , the equation cos ( 5 X ) = − 2 1 becomes 1 6 y 5 − 2 0 y 3 + 5 y = − 2 1 ⇔ ( 2 y + 1 ) ( 1 6 y 4 − 8 y 3 − 1 6 y 2 + 8 y + 1 ) = 0 . The quintic factor must have roots cos ( 1 5 2 π ) , cos ( 1 5 4 π ) , cos ( 1 5 8 π ) , cos ( 1 5 1 4 π ) .
We have g 1 ( Y ) : = 1 6 Y 4 − 8 Y 3 − 1 6 Y 2 + 8 Y + 1 whose roots are cos ( 1 5 2 π ) , cos ( 1 5 4 π ) , cos ( 1 5 8 π ) , cos ( 1 5 1 4 π ) .
Likewise, g 1 ( Y ) = 0 has roots cos 2 ( 1 5 2 π ) , cos 2 ( 1 5 4 π ) , cos 2 ( 1 5 8 π ) , cos 2 ( 1 5 1 4 π ) = cos 2 ( 1 5 π ) .
g 1 ( Y ) 1 6 Y 2 − 8 Y Y − 1 6 Y + 8 Y + 1 1 6 Y 2 − 1 6 Y + 1 ( 1 6 Y 2 − 1 6 Y + 1 ) 2 2 5 6 Y 4 − 5 7 6 Y 3 + 4 1 6 Y 2 − 9 6 Y + 1 = = = = = 0 0 8 Y ( Y − 1 ) ( 8 Y ) 2 ( Y − 1 ) 2 0
And so g 2 ( Y ) : = 2 5 6 Y 4 − 5 7 6 Y 3 + 4 1 6 Y 2 − 9 6 Y + 1 has roots cos 2 ( 1 5 2 π ) , cos 2 ( 1 5 4 π ) , cos 2 ( 1 5 8 π ) , cos 2 ( 1 5 π ) .
Furthermore, g 3 ( Y ) : = Y 4 ⋅ g 2 ( Y 1 ) = Y 4 − 9 6 Y 3 + 4 1 6 Y 2 − 5 7 6 Y + 2 5 6 has roots sec 2 ( 1 5 2 π ) , sec 2 ( 1 5 4 π ) , sec 2 ( 1 5 8 π ) , sec 2 ( 1 5 π ) .
Using the identity, we sec 2 ( Z ) − 1 = tan 2 ( Z ) , we have
f ( Y ) = g 3 ( Y + 1 ) = = ( Y + 1 ) 4 − 9 6 ( Y + 1 ) 3 + 4 1 6 ( Y + 1 ) 2 − 5 7 6 ( Y + 1 ) + 2 5 6 Y 4 − 9 2 Y 3 + 1 3 4 Y 2 − 2 8 Y + 1 has roots tan 2 ( 1 5 2 π ) , tan 2 ( 1 5 4 π ) , tan 2 ( 1 5 8 π ) , tan 2 ( 1 5 π ) . Hence, ( A , B , C , D ) = ( − 9 2 , 1 3 4 , 2 8 , 1 ) ⇒ A + 2 B + 3 C + 4 D = 9 6 .